Modeling growth, distribution, and the environment in a stock-flow consistent framework - Asjad Naqvi (WWWforEurope, 2015)
Economic policy in the EU faces a trilemma of solving three challenges simultaneously - growth, distribution, and the environment. In order to assess policies that address these issues simultaneously, economic models need to account for both sector-sector and sector-environment feedbacks within a single framework. This paper presents a multi-sectoral stock- flow consistent (SFC) macro model where a demand-driven economy consisting of multiple institutional sectors - firms, energy, households, government, and financial - interacts with the environment. The model is calibrated for the EU region and five policy scenarios are evaluated; low consumption, a capital stock damage function, carbon taxes, higher share of renewable energy, and technological shocks to productivity. Policy outcomes are tracked on overall output, unemployment, income and income distributions, energy, and emission levels. Results show that investment in mitigation technologies allows for absolute decoupling and ensures that the above three issues can be solved simultaneously.
Keywords: E12; E17; E23; E24; Q52; Q56; 330; ecological macroeconomics; stock-flow consistent; growth; distribution; environment; European Union